Creation Of Legal Basis Of Trade Union Organizations In Ferghana Valley - Abdulkhay Toshtukhtaevich Akhmedov (Zien Journals, 2025)
This article describes the processes of reforming the trade union system and the essence of effective solutions to the obstacles that are a source of it. Issues of the formation of the principles of democracy and transparency in the activities of trade unions are revealed.
Keywords: Trade unions; Trade unionsreform; Principles of democracy and transparency